Upaya Meningkatkan UMKM Ketupat Viral Desa Hamparan Perak Menggunakan Social Media - Mitha Zulaima; Tri Zahwanda; Salman Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are encouraged to leverage social media as an online marketing tool to reach a broader market. Currently, social media is easily accessible and widely favored by people worldwide. Therefore, MSME entrepreneurs are recommended to utilize social media as a means to share information about their products with consumers online. This research aims to assist and convince MSME entrepreneurs in Hamparan Perak Village about the benefits of social media for expanding their marketing reach. Through research on marketing enhancement strategies via social media, it can be determined how significant the impact and benefits of social media are for the development of MSME marketing in Hamparan Perak Village, Hamparan Perak District, Deli Serdang Regency.